A moderated mediation model of political collective action in Hong Kong: examining the roles of social media consumption and social identity. Issue 5 (3rd September 2017) - Ji, Yingru; Zhou, Yanmengqian; Kim, Sora
ABSTRACT: Adopting a communication mediation approach, this study explores the role of overall social networking service (SNS) use in facilitating people's participation in collective political action through the mediation of online and offline political discussions. The study also underscores the moderating effect on the mediation process of both social identity and geographical origin. Moderated mediation analyses reveal that the positive impact of overall SNS use on participation mediated by offline discussion is stronger for people with higher Hong Kong identity and for people from Hong Kong. This moderated mediation model specifies the socio-psychological mechanism of participation in collective political action in an immigrant society such as Hong Kong.